Microalgae Biorefinery Routes and Unit Operation Pre-Project Design, Selection and Sizing - Vilhena, Daniela Palma (2021)
Microalgae, or microscopic algae, have been studied as a natural marine resource for a number of economically relevant applications and several options exist for recovering and pro-cessing the biomass to obtain intracellular metabolites. This work presents the laboratory results from two proposed Nannochloropsis sp. microalgae biorefineries for the production of oil, high-value pigments, proteins and carbohydrates. Concerning the microalgal cell disruption processes, an overview of the technologies available was performed and bead milling was found to be potentially suitable for large scale microalgae biorefineries. Since petroleum-derived solvents such as dichloromethane, toluene or hexane are toxic and non-renewable, innovative and sustainable extractions using D-limonene, olive oil and etha-nol were tested to extract valuable lipids and pigments. Different membranes were also tested aiming the solvent recovery of ethanol and D-limonene. Regarding rejections of pigments and fatty acids, high values were achieved using organic solvent resistant membranes, proving to be possible to fractionate valuable biomolecules with a green and clean process. Afterwards, the laboratory results were extrapolated to mass balance calculations to select the biorefinery route by conducting a simplified economic analysis through equipment sizing and the cost estimation of the major equipments. The biorefinery route using olive oil as solvent was found to be the most promising process to study because, combined with the lower estimated CAPEX, the olive oil extract might be a highly profitable product rich in EPA fatty acid, as a product with significant health benefits for the human population.